Ethylenediamine-functionalized metal-organic frameworks for applications of electrochemical supercapacitors as an additive - Kalyon, Hilal Yildirim; Yilmaz, Ozan; Gencten, Metin; Gorduk, Semih; Sahin, Yucel (ELSEVIER SCIENCE SA, 2024)
In this study, the impact of incorporating ethylenediamine (ED)-functionalized metal-organic frameworks (MOFs) on enhancing the electrochemical performance of polypyrrole(PPy)-based conducting polymers as supercapacitor electrode materials was investigated. The stability of terephthalic acid-containing MOFs in different environments, including exposure to acids, relies on the specific metal ions and ligands utilized in their construction. In this research, ED treatment was chosen for its resistance to acid attack. Unlike the post-synthetic modifications observed in previous literature regarding ED-modified MOF5, this study introduces a unique approach where ED is directly integrated into the framework in a single step. The resulting materials, referred to as ED-MOF, were employed in creating a novel composite material concurrently with polypyrrole, designed for use as electrode materials in supercapacitor applications. The optimal loading in the electrochemical preparation of polypyrrole-based conducting polymers was determined using cyclic voltammetry and electrochemical impedance spectroscopy techniques. Areal capacitance for the resulting electrodes was evaluated through cyclic charge-discharge experiments. The areal capacitance of the ED-ZnMOF/1@/PPy/PGE electrode was found to be 575.2 mF.cm(-2) at a charge/discharge current density of 1 mA.cm(-2). This research underscores the potential advantages of combining conducting polymers and metal-organic frameworks in supercapacitors, as well as other electrochemical systems.
Keywords: Conducting polymers; Metal-organic frameworks; Ethylenediamine modification; Supercapacitors; CARBON-DIOXIDE CAPTURE; LITHIUM-ION BATTERIES; ENERGY-STORAGE; ELECTRODE MATERIALS; POLYPYRROLE; PERFORMANCE; CO2; NANOCOMPOSITE; COMPOSITES; TRANSPORT; Materials Science; Physics; Polymer Science